Sheehan’s syndrome complicated with Graves’ disease in a woman with a 20-year history of hypothyroidism - ManLi Yan; Jingyun Zhang; Yiting Wang; Hua Wei (Journal of International Medical Research)
Sheehan’s syndrome is a disorder caused by ischemic necrosis of the pituitary gland following postpartum hemorrhage, typically resulting in pituitary dysfunction that can affect the adrenal, thyroid, and gonadal axes. Clinically, patients may present with dysfunction of a single axis or multiple axes. The co-occurrence of Sheehan’s syndrome and Graves’ disease is extremely rare, posing a significant diagnostic challenge. Herein, we report the case of a woman in her early 50s with a 28-year history of Sheehan’s syndrome, which had led to complete pituitary dysfunction, who had been managing hypothyroidism for the past 20 years. However, over a 6-month period, she developed chronic diarrhea and showed progressive weight loss and laboratory results indicating hyperthyroidism. Based on further imaging and laboratory findings, along with her medical history, a diagnosis of Sheehan’s syndrome complicated with Graves’ disease was established, as evidenced by elevated levels of thyrotropin receptor antibodies. Treatment included adrenocorticotropic hormone replacement, antithyroid therapy, and other supportive measures. Although her gastrointestinal symptoms and weight loss resolved initially, the patient continued to experience persistent hyperthyroidism and elevated thyrotropin receptor antibody levels at the 20-month follow-up. This case highlights the need for regular endocrine monitoring in patients with Sheehan’s syndrome, particularly those with long-standing hypothyroidism, to promptly identify and address the potential overlap of autoimmune thyroid diseases.